Self-cleaning antibacterial coating and preparation method thereof

By using combined materials such as bisphenol A type epoxy resin in the coating, and adding nanosilver antibacterial agents and titanium sol agents, the problems of poor antibacterial performance and insufficient stability of existing coatings are solved, and efficient self-cleaning and antibacterial effects are achieved.

CN119639312BActive Publication Date: 2025-04-29GUANGDONG ORIENT RESIN
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510174210.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-18
Publication Date
2025-04-29
Estimated Expiration
2045-02-18

AI Technical Summary

Technical Problem

The existing coatings have poor antibacterial properties, difficult to coordinately improve self-cleaning and antibacterials, and their stability becomes poor under hot and cold shock and acid mist conditions, limiting product usage efficiency.

Method used

Bisphenol A type epoxy resin is used to combine leveling agent, silane coupling agent, curing agent and polyvinyl alcohol, and nanosilver antibacterial agent is added, and the cleaning, antibacterial properties and stability of the product are optimized through the coordinated formulation of titanium sol agent and filler agent.

Benefits of technology

It significantly improves the antibacterial properties and self-cleaning ability of the paint, ensures that the product has good stability under hot and cold shock and acid mist conditions, and improves the use efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of antibacterial coatings, in particular to a self-cleaning antibacterial coating and a preparation method thereof, comprising the following raw materials in parts by weight: 35-40 parts of bisphenol A epoxy resin, 30-35 parts of water, 8-12 parts of nano-silver antibacterial agent, 3-5 parts of leveling agent, 2-4 parts of silane coupling agent, 4-8 parts of curing agent, and 2-4 parts of polyvinyl alcohol. The self-cleaning antibacterial coating of the invention adopts bisphenol A epoxy resin, leveling agent, silane coupling agent, curing agent and polyvinyl alcohol, and the antibacterial property of the product is enhanced by adding the nano-silver antibacterial agent, and the titanium sol agent and the filler agent added at the same time are coordinated and coordinated, so that the cleaning and antibacterial of the product can be coordinated and improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of antibacterial coatings, and in particular to a self-cleaning antibacterial coating and a preparation method thereof. Background Art

[0002] Paint, traditionally known as paint in China, is a viscous liquid coated on the surface of an object to be protected or decorated, and can form a continuous film that is firmly attached to the object. It is usually mainly resin, oil, or emulsion, with or without pigments, fillers, and corresponding additives, and is prepared with organic solvents or water.

[0003] Existing coatings have poor antibacterial properties. At the same time, it is difficult to coordinate and improve the self-cleaning and antibacterial properties of the product. In addition, the product stability deteriorates under conditions of hot and cold shock and acid mist, which limits the efficiency of product use. Summary of the invention

[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a self-cleaning antibacterial coating and a preparation method thereof to solve the problems raised in the above background technology.

[0005] The present invention solves the technical problem by adopting the following technical solution:

[0006] The present invention provides a self-cleaning antibacterial coating, comprising the following raw materials in parts by weight:

[0007] 35-40 parts of bisphenol A epoxy resin, 30-35 parts of water, 8-12 parts of nano silver antibacterial agent, 3-5 parts of leveling agent, 2-4 parts of silane coupling agent, 4-8 parts of curing agent and 2-4 parts of polyvinyl alcohol.

[0008] Preferably, the leveling agent is a polysiloxane polyether copolymer leveling agent; the silane coupling agent is silane coupling agent KH560; and the curing agent is triethanolamine;

[0009] The antibacterial coating also includes 4-7 parts of titanium sol and 3-5 parts of filler;

[0010] The preparation method of the titanium sol agent is as follows:

[0011] S1: adding the yttrium solution to the sodium dodecylbenzene sulfonate solution at a weight ratio of 3:5, then adding 10-15% of alginic acid and 2-5% of silane coupling agent KH550 based on the total weight of the yttrium solution, stirring thoroughly to obtain a yttrium liquid;

[0012] S2: Stir and mix spodumene in a sufficient amount of acid solution, then wash, filter and dry, and mix the dried spodumene and dopamine hydrochloride solution in a weight ratio of 2:5 to obtain a spodumene regulator;

[0013] S3: First add 2-5 parts by weight of titanium sol into 4-7 parts by weight of yttrium liquid, then add 2-5 parts by weight of spodumene regulator and mix thoroughly, finally filter and dry to obtain titanium sol.

[0014] Preferably, the mass fraction of the sodium dodecylbenzene sulfonate solution is 2-5%; and the acid solution is a sulfuric acid solution with a mass fraction of 5%.

[0015] Preferably, the particle size of the titanium sol is 10-15 nm; and the mass fraction of the dopamine hydrochloride solution is 3-5%.

[0016] Preferably, the preparation method of the filler is:

[0017] S11: zirconium silicate and 5% by mass sodium lignin sulfonate solution are mixed in a weight ratio of 2:5 to obtain a zirconium silicate solution;

[0018] S12: adding 5-10% of the total weight of the zirconium silicate liquid activated calcium carbonate and 2-5% of the total weight of the zirconium silicate liquid stearic acid to the zirconium silicate liquid, blending and ball milling, after the ball milling is completed, washing and drying to obtain a filler.

[0019] Preferably, the blending process is performed at a ball milling speed of 1000-1500 r / min, and the ball milling is performed for 2 hours.

[0020] Preferably, the activated calcium carbonate is nano-calcium carbonate and lanthanum chloride solution which are fully stirred in a weight ratio of 2:5, then filtered and dried, and then treated in a plasma box for 10-15 minutes at a treatment power of 300 W. After the treatment is completed, activated calcium carbonate is obtained.

[0021] Preferably, the mass fraction of the lanthanum chloride solution is 2-5%.

[0022] The present invention also provides a method for preparing a self-cleaning antibacterial coating, comprising the following steps: weighing raw materials according to weight portions, and then mixing the raw materials to obtain the self-cleaning antibacterial coating of the present invention.

[0023] Preferably, the hot pressing treatment pressure is 5 MPa.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The self-cleaning antibacterial coating of the present invention adopts bisphenol A type epoxy resin to match leveling agent, silane coupling agent, curing agent and polyvinyl alcohol, and by adding nano silver antibacterial agent, the antibacterial property of the product is enhanced, and the titanium sol agent and filler agent added at the same time are coordinated and coordinated, so that the cleaning and antibacterial properties of the product can be coordinated and improved, and the product stability effect is remarkable under the conditions of hot and cold shock and acid mist of the product; the titanium sol agent is blended with yttrium solution, sodium dodecylbenzene sulfonate solution, alginic acid and silane coupling agent KH550, and by adding spodumene regulator to match titanium sol, lithium The spodumene in the pyroxene regulator is added to a sufficient amount of acid solution to optimize the activity, and then combined with dopamine hydrochloride solution to better blend the yttrium solution, so that the prepared titanium sol has more obvious coordination improvement in product performance in the system, and the zirconium silicate in the filler is combined with sodium lignin sulfonate solution to optimize its dispersion, and then blended with nano calcium carbonate and lanthanum chloride solution, and then plasma-treated to obtain the active calcium carbonate and coordinate with the zirconium silicate solution, so that the prepared filler and the titanium sol are more significantly coordinated, thereby further improving the performance of the obtained product. DETAILED DESCRIPTION

[0026] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] The self-cleaning antibacterial coating of this embodiment includes the following raw materials in parts by weight:

[0028] 35-40 parts of bisphenol A epoxy resin, 30-35 parts of water, 8-12 parts of nano silver antibacterial agent, 3-5 parts of leveling agent, 2-4 parts of silane coupling agent, 4-8 parts of curing agent and 2-4 parts of polyvinyl alcohol.

[0029] The leveling agent of this embodiment is a polysiloxane polyether copolymer leveling agent; the silane coupling agent is silane coupling agent KH560; and the curing agent is triethanolamine.

[0030] The antibacterial coating of this embodiment also includes 4-7 parts of titanium sol agent and 3-5 parts of filler agent;

[0031] The preparation method of the titanium sol agent is as follows:

[0032] S1: adding the yttrium solution to the sodium dodecylbenzene sulfonate solution at a weight ratio of 3:5, then adding 10-15% of alginic acid and 2-5% of silane coupling agent KH550 based on the total weight of the yttrium solution, stirring thoroughly to obtain a yttrium liquid;

[0033] S2: Stir and mix spodumene in a sufficient amount of acid solution, then wash, filter and dry, and mix the dried spodumene and dopamine hydrochloride solution in a weight ratio of 2:5 to obtain a spodumene regulator;

[0034] S3: First add 2-5 parts by weight of titanium sol into 4-7 parts by weight of yttrium liquid, then add 2-5 parts by weight of spodumene regulator and mix thoroughly, finally filter and dry to obtain titanium sol.

[0035] The mass fraction of the sodium dodecylbenzene sulfonate solution in this embodiment is 2-5%; the acid solution is a sulfuric acid solution with a mass fraction of 5%.

[0036] The particle size of the titanium sol in this embodiment is 10-15 nm; the mass fraction of the dopamine hydrochloride solution is 3-5%.

[0037] The preparation method of the filler of this embodiment is:

[0038] S11: zirconium silicate and 5% by mass sodium lignin sulfonate solution are mixed in a weight ratio of 2:5 to obtain a zirconium silicate solution;

[0039] S12: adding 5-10% of the total weight of the zirconium silicate liquid activated calcium carbonate and 2-5% of the total weight of the zirconium silicate liquid stearic acid to the zirconium silicate liquid, blending and ball milling, after the ball milling is completed, washing and drying to obtain a filler.

[0040] The ball milling speed of the blended ball milling treatment in this embodiment is 1000-1500 r / min, and the ball milling is 2 h.

[0041] The activated calcium carbonate of this embodiment is a solution of nano calcium carbonate and lanthanum chloride, which are stirred fully in a weight ratio of 2:5, then filtered and dried, and then treated in a plasma box for 10-15 minutes at a processing power of 300 W. After the treatment, activated calcium carbonate is obtained.

[0042] The mass fraction of the lanthanum chloride solution of the present embodiment is 2-5%.

[0043] The present invention also provides a method for preparing a self-cleaning antibacterial coating, comprising the following steps: weighing raw materials according to weight portions, and then mixing the raw materials to obtain the self-cleaning antibacterial coating of the present invention.

[0044] Example 1.

[0045] The self-cleaning antibacterial coating of this embodiment includes the following raw materials in parts by weight:

[0046] 35 parts of bisphenol A epoxy resin, 30 parts of water, 8 parts of nano silver antibacterial agent, 3 parts of leveling agent, 2 parts of silane coupling agent, 4 parts of curing agent, and 2 parts of polyvinyl alcohol.

[0047] The leveling agent of this embodiment is a polysiloxane polyether copolymer leveling agent; the silane coupling agent is silane coupling agent KH560; and the curing agent is triethanolamine.

[0048] The antibacterial coating of this embodiment also includes 4 parts of titanium sol agent and 3 parts of filler agent;

[0049] The preparation method of the titanium sol agent is as follows:

[0050] S1: adding the yttrium solution to the sodium dodecylbenzene sulfonate solution at a weight ratio of 3:5, then adding 10% of the total weight of the yttrium solution in alginate and 2% of the total weight of the silane coupling agent KH550 in the yttrium solution, stirring thoroughly to obtain a yttrium liquid;

[0051] S2: Stir and mix spodumene in a sufficient amount of acid solution, then wash, filter and dry, and mix the dried spodumene and dopamine hydrochloride solution in a weight ratio of 2:5 to obtain a spodumene regulator;

[0052] S3: First, add 2 parts by weight of titanium sol into 4 parts by weight of yttrium liquid, then add 2 parts by weight of spodumene regulator and mix thoroughly, and finally filter and dry to obtain titanium sol.

[0053] The mass fraction of the sodium dodecylbenzene sulfonate solution in this embodiment is 2%; the acid solution is a sulfuric acid solution with a mass fraction of 5%.

[0054] The particle size of the titanium sol in this embodiment is 10 nm; the mass fraction of the dopamine hydrochloride solution is 3%.

[0055] The preparation method of the filler of this embodiment is:

[0056] S11: zirconium silicate and 5% by mass sodium lignin sulfonate solution are mixed in a weight ratio of 2:5 to obtain a zirconium silicate solution;

[0057] S12: Add 5% of the total weight of the zirconium silicate liquid activated calcium carbonate and 2% of the total weight of the zirconium silicate liquid stearic acid to the zirconium silicate liquid, blend and ball-mill, and after the ball-milling is completed, wash with water and dry to obtain a filler.

[0058] The ball milling speed of the blended ball milling treatment in this embodiment is 1000 r / min, and the ball milling is performed for 2 h.

[0059] The activated calcium carbonate of this embodiment is nano calcium carbonate and lanthanum chloride solution which are fully stirred in a weight ratio of 2:5, then filtered and dried, and then treated in a plasma box for 10 minutes at a processing power of 300 W. After the treatment, activated calcium carbonate is obtained.

[0060] The mass fraction of the lanthanum chloride solution of the present embodiment is 2%.

[0061] The present invention also provides a method for preparing a self-cleaning antibacterial coating, comprising the following steps: weighing raw materials according to weight portions, and then mixing the raw materials to obtain the self-cleaning antibacterial coating of the present invention.

[0062] Example 2.

[0063] The self-cleaning antibacterial coating of this embodiment includes the following raw materials in parts by weight:

[0064] 40 parts of bisphenol A epoxy resin, 35 parts of water, 12 parts of nano silver antibacterial agent, 5 parts of leveling agent, 4 parts of silane coupling agent, 8 parts of curing agent, and 4 parts of polyvinyl alcohol.

[0065] The leveling agent of this embodiment is a polysiloxane polyether copolymer leveling agent; the silane coupling agent is silane coupling agent KH560; and the curing agent is triethanolamine.

[0066] The antibacterial coating of this embodiment also includes 7 parts of titanium sol agent and 5 parts of filler agent;

[0067] The preparation method of the titanium sol agent is as follows:

[0068] S1: adding the yttrium solution to the sodium dodecylbenzene sulfonate solution at a weight ratio of 3:5, then adding 15% of the total weight of the yttrium solution in alginate and 5% of the total weight of the silane coupling agent KH550 in the yttrium solution, stirring thoroughly to obtain a yttrium liquid;

[0069] S2: Stir and mix spodumene in a sufficient amount of acid solution, then wash, filter and dry, and mix the dried spodumene and dopamine hydrochloride solution in a weight ratio of 2:5 to obtain a spodumene regulator;

[0070] S3: First, add 5 parts by weight of titanium sol into 7 parts by weight of yttrium liquid, then add 5 parts by weight of spodumene regulator and mix thoroughly, and finally filter and dry to obtain titanium sol.

[0071] The mass fraction of the sodium dodecylbenzene sulfonate solution in this embodiment is 5%; the acid solution is a sulfuric acid solution with a mass fraction of 5%.

[0072] The particle size of the titanium sol in this embodiment is 15 nm; the mass fraction of the dopamine hydrochloride solution is 5%.

[0073] The preparation method of the filler of this embodiment is:

[0074] S11: zirconium silicate and 5% by mass sodium lignin sulfonate solution are mixed in a weight ratio of 2:5 to obtain a zirconium silicate solution;

[0075] S12: adding activated calcium carbonate (10% by weight of the total weight of the zirconium silicate liquid) and stearic acid (5% by weight of the total weight of the zirconium silicate liquid) to the zirconium silicate liquid, blending and ball milling, and after the ball milling is completed, washing and drying to obtain a filler.

[0076] The ball milling speed of the blended ball milling treatment in this embodiment is 1500r / min, and the ball milling is performed for 2h.

[0077] The activated calcium carbonate of this embodiment is nano calcium carbonate and lanthanum chloride solution which are fully stirred in a weight ratio of 2:5, then filtered and dried, and then treated in a plasma box for 15 minutes at a processing power of 300 W. After the treatment is completed, activated calcium carbonate is obtained.

[0078] The mass fraction of the lanthanum chloride solution of the present embodiment is 5%.

[0079] The present invention also provides a method for preparing a self-cleaning antibacterial coating, comprising the following steps: weighing raw materials according to weight portions, and then mixing the raw materials to obtain the self-cleaning antibacterial coating of the present invention.

[0080] Example 3.

[0081] The self-cleaning antibacterial coating of this embodiment includes the following raw materials in parts by weight:

[0082] 37.5 parts of bisphenol A epoxy resin, 32.5 parts of water, 10 parts of nano silver antibacterial agent, 4 parts of leveling agent, 3 parts of silane coupling agent, 6 parts of curing agent, and 3 parts of polyvinyl alcohol.

[0083] The leveling agent of this embodiment is a polysiloxane polyether copolymer leveling agent; the silane coupling agent is silane coupling agent KH560; and the curing agent is triethanolamine.

[0084] The antibacterial coating of this embodiment also includes 5.5 parts of titanium sol agent and 4 parts of filler agent;

[0085] The preparation method of the titanium sol agent is as follows:

[0086] S1: adding the yttrium solution to the sodium dodecylbenzene sulfonate solution at a weight ratio of 3:5, then adding 12.5% ​​of the total weight of the yttrium solution in alginate and 3.5% of the total weight of the yttrium solution in a silane coupling agent KH550, and stirring thoroughly to obtain a yttrium liquid;

[0087] S2: Stir and mix spodumene in a sufficient amount of acid solution, then wash, filter and dry, and mix the dried spodumene and dopamine hydrochloride solution in a weight ratio of 2:5 to obtain a spodumene regulator;

[0088] S3: 3.5 parts by weight of titanium sol are first added to 5.5 parts of yttrium liquid, and then 3.5 parts by weight of spodumene regulator are added and mixed thoroughly, and finally filtered and dried to obtain titanium sol.

[0089] The mass fraction of the sodium dodecylbenzene sulfonate solution in this embodiment is 3.5%; the acid solution is a sulfuric acid solution with a mass fraction of 5%.

[0090] The particle size of the titanium sol in this embodiment is 12.5 nm; the mass fraction of the dopamine hydrochloride solution is 4%.

[0091] The preparation method of the filler of this embodiment is:

[0092] S11: zirconium silicate and 5% by mass sodium lignin sulfonate solution are mixed in a weight ratio of 2:5 to obtain a zirconium silicate solution;

[0093] S12: Add 7.5% of the total weight of the zirconium silicate liquid activated calcium carbonate and 3.5% of the total weight of the zirconium silicate liquid stearic acid to the zirconium silicate liquid, blend and ball-mill, and after the ball-milling is completed, wash with water and dry to obtain a filler.

[0094] The ball milling speed of the blended ball milling treatment in this embodiment is 1250 r / min, and the ball milling is performed for 2 h.

[0095] The activated calcium carbonate of this embodiment is a solution of nano-calcium carbonate and lanthanum chloride, which are stirred fully in a weight ratio of 2:5, then filtered and dried, and then treated in a plasma box for 12.5 minutes at a processing power of 300 W. After the treatment, activated calcium carbonate is obtained.

[0096] The mass fraction of the lanthanum chloride solution of the present embodiment is 3.5%.

[0097] The present invention also provides a method for preparing a self-cleaning antibacterial coating, comprising the following steps: weighing raw materials according to weight portions, and then mixing the raw materials to obtain the self-cleaning antibacterial coating of the present invention.

[0098] Comparative Example 1.

[0099] The difference from Example 3 is that no titanium sol agent is added.

[0100] Comparative Example 2.

[0101] The difference from Example 3 is that no yttrium liquid is added in the preparation of the titanium sol.

[0102] Comparative Example 3.

[0103] The difference from Example 3 is that no titanium sol is added to the titanium sol agent.

[0104] Comparative Example 4.

[0105] The difference from Example 3 is that no spodumene regulator is added to the titanium sol.

[0106] Comparative Example 5.

[0107] The difference from Example 3 is that no filler is added.

[0108] Comparative Example 6.

[0109] The difference from Example 3 is that no active calcium carbonate is added to the filler.

[0110] In order to compare and illustrate the performance of different products, the following properties of the products obtained in the embodiments and comparative examples were tested, and the test results are as follows.

[0111] The performance of the products of Examples 1-3 and Comparative Examples 1-6 was routinely tested. The products were placed in 2% hydrochloric acid mist for 12 hours, then placed at 75°C for 12 hours, and subjected to cold water shock for 2 minutes with an impact strength of 5 MPa. The above was one cycle. The test was repeated 5 times to test the acid corrosion resistance and cold and hot shock resistance. The test was as follows:

[0112]

[0113] It can be seen from Comparative Examples 1-6 and Example 3 that the product of Example 3 has excellent antibacterial rate of Escherichia coli and anti-fouling self-cleaning properties, and the product has significant acid and rot resistance and thermal shock resistance stability.

[0114] If neither titanium sol nor filler is added to the product, the product performance will deteriorate significantly. If both are used in combination, the product performance effect will be most obvious.

[0115] When no yttrium liquid, no titanium sol, no spodumene regulator, and no activated calcium carbonate are added to the titanium sol in the preparation of the titanium sol, the performance of the products tends to deteriorate. Only the titanium sol and filler prepared by the method of the present invention have significant improvement effects.

[0116] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0117] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. Self-cleaning antibacterial coating, characterized in that: It includes the following raw materials in parts by weight: 35-40 parts of bisphenol A epoxy resin, 30-35 parts of water, 8-12 parts of nano silver antibacterial agent, 3-5 parts of leveling agent, 2-4 parts of silane coupling agent, 4-8 parts of curing agent, 2-4 parts of polyvinyl alcohol; The antibacterial coating also includes 4-7 parts of titanium sol and 3-5 parts of filler; The preparation method of the titanium sol agent is as follows: S1: adding the yttrium solution to the sodium dodecylbenzene sulfonate solution at a weight ratio of 3:5, then adding 10-15% of alginic acid and 2-5% of silane coupling agent KH550 based on the total weight of the yttrium solution, stirring thoroughly to obtain a yttrium liquid; S2: Stir and mix spodumene in a sufficient amount of acid solution, then wash, filter and dry, and mix the dried spodumene and dopamine hydrochloride solution in a weight ratio of 2:5 to obtain a spodumene regulator; S3: first adding 2-5 parts by weight of titanium sol to 4-7 parts by weight of yttrium liquid, then adding 2-5 parts by weight of spodumene regulator and blending them thoroughly, and finally filtering and drying to obtain titanium sol; The preparation method of the filler is: S11: zirconium silicate and 5% by mass sodium lignin sulfonate solution are mixed in a weight ratio of 2:5 to obtain a zirconium silicate solution; S12: adding 5-10% of the total weight of the zirconium silicate liquid activated calcium carbonate and 2-5% of the total weight of the zirconium silicate liquid stearic acid to the zirconium silicate liquid, blending and ball milling, washing and drying after the ball milling, to obtain a filler; The activated calcium carbonate is a solution of nano calcium carbonate and lanthanum chloride, which are stirred in a weight ratio of 2:5, and then filtered and dried, and then treated in a plasma box for 10-15 minutes with a treatment power of 300W. After the treatment is completed, the activated calcium carbonate is obtained.

2. The self-cleaning antibacterial coating according to claim 1, characterized in that: The leveling agent is a polysiloxane polyether copolymer leveling agent; the silane coupling agent is silane coupling agent KH560; and the curing agent is triethanolamine.

3. The self-cleaning antibacterial coating according to claim 1, characterized in that: The mass fraction of the sodium dodecylbenzene sulfonate solution is 2-5%; the acid solution is a sulfuric acid solution with a mass fraction of 5%.

4. The self-cleaning antibacterial coating according to claim 1, characterized in that: The particle size of the titanium sol is 10-15 nm; the mass fraction of the dopamine hydrochloride solution is 3-5%.

5. The self-cleaning antibacterial coating according to claim 1, characterized in that: The blending process is performed at a ball milling speed of 1000-1500 r / min, and the ball milling is performed for 2 hours.

6. The self-cleaning antibacterial coating according to claim 1, characterized in that: The mass fraction of the lanthanum chloride solution is 2-5%.

7. A method for preparing the self-cleaning antibacterial coating according to any one of claims 1 to 6, characterized in that: The following steps are involved: The raw materials are weighed according to weight, and then mixed thoroughly to obtain a self-cleaning antibacterial coating.

Citation Information

Patent Citations

  • Organic-inorganic antibacterial antifouling interior wall coating and preparation method thereof

    CN118307996A

  • KR20230141064A